2023
DOI: 10.29026/oea.2023.220133
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring spatiotemporal dynamics of plasmonic vortices

Abstract: Plasmonic vortices confining orbital angular momentums to surface have aroused wide research interest in the last decade. Recent advances of near-field microscopes have enabled the study on the spatiotemporal dynamics of plasmonic vortices, providing a better understanding of optical orbital angular momentums in the evanescent wave regime. However, these works only focused on the objective characterization of plasmonic vortex and have not achieved subjectively tailoring of its spatiotemporal dynamics for speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…As illustrated in Fig. 11(b), Yuan et al demonstrated that different coupler designs can even affect the spatiotemporal dynamics of plasmonic vortices with the same topological charge [299] . Yang et al found unexpected spiral phases in the center of generated plasmonic vortices and demonstrated the existence of deuterogenic plasmonic vortices, as shown in Fig.…”
Section: On-chip Tailoring Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Fig. 11(b), Yuan et al demonstrated that different coupler designs can even affect the spatiotemporal dynamics of plasmonic vortices with the same topological charge [299] . Yang et al found unexpected spiral phases in the center of generated plasmonic vortices and demonstrated the existence of deuterogenic plasmonic vortices, as shown in Fig.…”
Section: On-chip Tailoring Devicesmentioning
confidence: 99%
“…(b) Schematic of the temporal evolution progress of plasmonic vortices with the same topological charge generated by different couplers. Reproduced from an open access reference [299]. (c) Schematic of deuterogenic plasmonic vortex in the center of generated plasmonic vortex with higher topological charge.…”
Section: On-chip Tailoring Devicesmentioning
confidence: 99%
“…Metasurfaces, with their unprecedented flexibility to manipulate light at the subwavelength scale, have been widely utilized for exotic functional devices. In addition to free space light manipulation, metasurfaces can also be extensively incorporated into on-chip devices to efficiently modulate guided electromagnetic waves, known as meta-waveguide . Recently, on-chip metalens, polarization rotators, mode converters, and free-space light couplers have been designed based on chip-integrated metasurface. Moreover, metasurface-assisted waveguide couplers designed based on phase matching conditions and the spin-momentum locking effect can be spin-, mode-, and wavelength-demultiplexing.…”
Section: Introductionmentioning
confidence: 99%
“…Since Arthur Ashkin pioneered the development of optical beams that can precisely manipulate micro/nanoparticles [1], many researchers have stabilized the capture of particles by increasing gradient and radiation forces [2][3][4][5]. However, these methods exhibit limitations such as difficulty in maintaining stable capture in the far field.…”
Section: Introductionmentioning
confidence: 99%